Frequency and Type of Red Cell Alloimmunization in Blood Transfusion Dependent Patients of β – Thalassaemia Major (Medical Forum Monthly, 2024)
Objective: To determine red cell alloimmunization in blood transfusion dependent patients of β – thalassaemia major by measuring it’s frequency and type.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the blood bank of Benazir Bhutto Hospital, Rawalpindi from December 2010 to December 2011Materials and Methods: 150 patients of beta thalassaemia major, according to inclusion criteria were enrolled in the study. Indirect Coombs’ test ( ICT) was performed on serum of all these patients for antibody detection. Patients with positive ICT were subjected to panel test to detect the type of alloantibody.Results: All the statistical analysis was done using SPSS version 10.0.Out of 150 patients, 90 were males (60%) and 60 were females (40%).The age of patients ranged between 4 and 18 years with mean age of 8.78 years(±4.15).ICT was positive in 8 (5.3%) patients. Panel test showed six alloantibodies. one patient had two antibodies while all other patients had single antibody. Alloantibodies detected were anti E in 3 patients(37.5%) while one patient each had anti C(12.5%), anti D(12.5%),anti e(12.5%) and anti D(12.5%).One patient had anti E + anti K(12.5%).Conclusion: The study showed that alloimmunization to red cell antigens is an important complication of blood transfusion. Most of the alloantibodies were against Rh antigens. Hence it is recommended that blood should be matched at least for Rh antigens from the start of transfusion.